LINEAR SUBSTRUCTURES IN GALAXY CLUSTERS - Panko, E.; Korshunov, V.; Yemelianov, S.; Zabolotnii, V. (Одеські астрономічні публікації, 2019)
We propose detailed scheme that is describing the morphology of linear substructures in galaxy clusters. Our base morphological scheme di- vides galaxy clusters using numerical criteria according the parameters: concentration to the cluster center, the presence of linear substructure, orientation of images of galaxies, the role of brightest cluster members, the shape of galaxies. Our analysis of 2D distribution of galaxies based on study more than 500 galaxy clusters. We show the linear substructures are regular peculiarity in galaxy clusters. Our approach allows to divide filamentary and edge-on wall substructures and to select galaxy clusters with possible peculiarities in hot gas and/or DM distribution.